Introduction to micro- and nano-motors - Zhang, Li; Pumera, Martin; Sánchez, Samuel; Ma, Xing (Nanoscale, 2024)
An introduction to the Nanoscale and Journal of Materials Chemistry B themed collection on micro- and nano-motors that features a series of articles discussing the virtue of their small size and controllable mobility, while highlighting the revolutionary potential applications.